First analysis of 10‐year trends in national factor concentrates usage in haemophilia: data from CHARMS, the Canadian Hemophilia Assessment and Resource Management System. (July 2014) - Traore, A. N.; Chan, A. K. C.; Webert, K. E.; Heddle, N.; Ritchie, B.; St‐Louis, J.; Teitel, J.; Lillicrap, D.; Iorio, A.; Walker, I.
Summary: The Canadian Hemophilia Assessment and Resource Management System (CHARMS) tracks factor concentrates (FC) from the sole suppliers, Canadian Blood Services (CBS) and Hema‐Quebec (HQ), to hospitals and to patients' homes. Patients FC infusion data are entered into CHARMS at Canadian Hemophilia Treatment Centres (HTCs) then exported to the national database (CentrePoint). From 2000 to 2009, 2260 registered haemophilia A or B patients received FVIII (1 009 097 765 IU) and FIX (272 406 859 IU). Over 91% of FVIII and over 84% of FIX was infused at home. Utilization of FVIII progressively increased; this was accounted for by an increase in the number of patients treated ( r  = 0.97; P  <   0.001), there being a linear relationship between the increase in utilization and the increase in number of patients treated ( P  <   0.001). There was also a correlation with the annual amount used per patient ( r  =   0.95; P  <   0.001). Utilization of FIX did not increase over time. The highest proportional utilization of both FVIII and FIX was for prophylaxis, and this proportion progressively increased being, in year 10 (2009), 77% and 66% for FVIII and FIX respectively. The proportion used for bleeding remained steady; in year 10 that proportion was 14% for FVIII and 26% for FIX, the use per patient for bleeding decreasing. The HTC‐based CHARMS tracking system is essential, in Canada, for analysing indications for infusion, for predicting utilization and planning for future needs.